Application progress of Traditional Chinese Medicine nursing techniques for patients with cough variant asthma (中医护理技术在咳嗽变异性哮喘中的应用进展) - WANG Yanli (王彦丽); WANG Yingzhe (王英哲); XUE Li (薛丽) (中西医结合护理)
The clinical manifestations of cough variant asthma (CVA ) are mostly cough without asthma, which is easily misdiagnosed and mistreated and transformed into typical asthma. This article summarizes the pathogenesis of CVA and the application effects of TCM nursing technology in CVA patients, aiming to provide reference and evidence support for improving the clinical symptoms of CVA patients and improving the quality of life. (咳嗽变异性哮喘(CVA)临床表现多为只咳不喘, 诊治时应注意鉴别区分。本文对CVA发病机制及中医护理技术如拔罐法、刮痧疗法、耳穴埋豆等在CVA患者中的应用效果进行总结, 旨在为改善CVA患者临床症状, 提高生活质量提供参考和证据支持。)